Do clinical characteristics predict the cognitive course in early‐onset schizophrenia‐spectrum disorders?. (24th March 2018) - Teigset, Charlotte M.; Mohn, Christine; Brunborg, Cathrine; Juuhl‐Langseth, Monica; Holmén, Aina; Rund, Bjørn Rishovd
Abstract : Background: Being in a period with extensive brain maturation, adolescents with early‐onset schizophrenia‐spectrum disorders (EOS) provide unique neurodevelopmental data that may contribute to a better understanding of schizophrenia at all ages. Cognitive dysfunction is a central feature of schizophrenia and is more pronounced in EOS than in later onset illness. However, there is limited research on both the long‐term course of global cognition in EOS, and how cognition over time is influenced by clinical characteristics during the early illness period. Methods: Thirty‐one EOS patients and 73 controls (age 12–18) were assessed on clinical variables at baseline (PANSS, duration of untreated psychosis [DUP], hospitalizations, suicide attempts, and remission). Neuropsychological assessments with the MATRICS Consensus Cognitive Battery (MCCB) were conducted at baseline and after both 1 and 2 years, and composite scores of total performances were calculated. The analyses were performed with a linear mixed model. Results: The present study found that global cognition followed a stable course over the first years of the disease in EOS, though at a significantly lower level in EOS compared with the controls. We did not detect a relationship between DUP, remission, positive/negative symptoms, and hospitalizations on one hand, and long‐term cognition on the other hand, but PANSS‐general and suicide attempt history at baseline were identified as risk factors of longitudinal cognitive function. Conclusions: Though at different levels, the EOS group and the controls had a similar cognitive course over 2 years. Some baseline characteristics (psychotic symptoms, DUP, remission, and hospitalization) had no influence on cognition within the first 2 years of illness. In contrast, general symptoms and a history of suicide attempts at baseline were more potent risk factors of the cognitive course than the psychotic‐specific symptoms, and should, therefore, be subject to specific attention in the evaluation and treatment of patients with early‐onset psychosis.